(untitled) (International Journal of Physiotherapy, 2016)
Background: Postural control requires complex processing of peripheral sensory inputs from the visual, somatosensory and vestibular systems. Motion sensitivity and decreased postural control are influenced by visual-vestibular conflicts.The purpose of this study was to measure the difference between the postural control of healthy adults with and without history of sub-clinical chronic motion sensitivity using a computerized dynamic posturography in a virtual reality environment. Sub-clinical chronic motion sensitivity was operationally defined as a history of avoiding activities causing dizziness, nausea, imbalance, and/or blurred vision without having a related medical diagnosis. Methods: Twenty healthy adults between 22 and 33 years of age participated in the study. Eleven subjects had sub-clinical chronic motion sensitivity and 9 subjects did not. Postural control was measured in both groups using the Bertec Balance Advantage-Dynamic Computerized Dynamic Posturography with Immersion Virtual Reality (CDP-IVR). The CDP-IVR reports an over-all equilibrium score based on subjects’ center of gravity displacement and postural sway while immersed in a virtual reality environment. Subjects were tested on stable (condition 1) and unstable (condition2) platform conditions. Results: There was no significant difference between the two groups in terms of mean age, height, weight, body mass index in kg/m2, postural control scores for conditions 2, and average (p>0.05). However, significant differences were observed in mean postural control for condition 1 between groups (p=0.03). Conclusions: Results of this study suggest that healthy young adults without chronic sub-clinical motion sensitivity have better postural control than those with chronic sub-clinical motion sensitivity. Further investigation is warranted to explore wider age ranges with larger samples sizes as well as intervention strategies to improve postural control.